Low‐profile dual‐band antenna with on‐demand beam switching capabilities. Issue 1 (19th September 2019) - Iqbal, Amjad; Bouazizi, Amal; Smida, Amor; Basir, Abdul; Naeem, Umair
Abstract : In this study, a dual‐band pattern‐reconfigurable monopole antenna is designed and experimentally validated for C ‐band satellite communication systems and sensing UWB‐radar applications. The proposed antenna has three resonances at 3, 7 and, 8.5 GHz. To incorporate the reconfigurability, two switches are applied in the ground plane to reshape the radiation pattern and focus the radiated power in the desired direction. Thus, the desired beam from the antenna can be obtained by adjusting the states of the switches. The proposed antenna has good impedance matching ( S 11 < − 10 dB for both operating bands), reasonable gain (>4.1 dBi), and high efficiency (>83%) for all switching states. A good agreement is observed between the simulated and measured results.